Empowering women through gender friendly technologies in agriculture - Joshi, Pratibha; Sharma, J.P.; Sharma, Nishi; Singh, O.P.; Dabas, J.P.S.; Raksha, Raksha; Mahra, Grijesh (Annals of Agricultural Research, 2019)
Agriculture is an important component of rural livelihoods. Almost 70% of India’s population of 1.2 billion- some 833 million persons lives in rural areas. Women play a pivotal role in all agricultural activities from sowing to post harvest work. Woman is the backbone of Indian agricultural workforce and doing the most tedious and back-breaking tasks in agriculture and household chores. Drudgery of farm women is an important aspect that has attracted wide attention of researchers. The progress of farm mechanization in terms of demand of agricultural equipment is estimated at about 1 to 1.5 per cent per annum. Mechanization with gender specific domain can only alleviate the burden of women farmers. Some commendable work has been done to develop agriculture with major emphasis technologies for drudgery reduction with gender issues in rural sector with an intent to understand the women technological needs which is different than men due to their different physiological and ergonomical variations. Therefore in this paper gender specific farm tools and techniques were highlighted. Improvement in the practices and development of ergonomically suitable implements for agriculture related operations is helpful to reduce drudgery and to achieve higher production in an efficient manner.